Impact of COVID-19 on BMI at EdTech startups - Ulanova, Yana (2021)
COVID-19 occurred at the end of 2019 and forced the world to change daily routines. Schools and offices were closed and needed to move to online mode, and parents stayed at home with children. Meanwhile, teachers faced difficult situations where they had to learn how to teach online and make sure that students stay focused. Educational technology (EdTech) aims to advance the learning results for students, foster individual approaches, and diminish teachers' burnout. Hence, EdTech (educational technology) startups ended up in an interesting situation because of the pandemic. The study aims to understand the impact of COVID-19 on business model innovation at EdTech startups. The business model is a relatively young concept, and researchers still cannot agree on one definition due to its complexity. Thus, the author asked EdTech startups how they describe it. The research questions for the study are the following. First, how did COVID-19 impact the EdTech industry? Second, what happened in BMI (busi-ness model innovation) due to COVID-19? The author did semi-structured interviews with 16 companies (two industry experts and 14 EdTech startups). The author analyzed data from the interviews with the thematic content analysis. The findings reveal that COVID-19 had both positive and negative impacts on EdTech startups. Due to the pandemic, there is no more need for EdTech startups to prove that educational technology is needed for schools. Second, teachers became more open to utilizing solutions in remote classrooms. Third, EdTech startups enhanced the user base and received valuable feedback from users—lastly, the industry experience rapid growth and interest from investors. As for negatives, potential and future sales discussions were put on hold or canceled. EdTech startups could not open new markets due to travel limitations. Overall, EdTech startups did not invent a new business model but rather innovated its elements.